2022
DOI: 10.1002/ange.202203673
|View full text |Cite
|
Sign up to set email alerts
|

Stereoinvertive Nucleophilic Substitution at Quaternary Carbon Stereocenters of Cyclopropyl Ketones and Ethers

Abstract: A highly regio-and diastereoselective nucleophilic substitution at the quaternary carbon stereocenter of cyclopropyl ketones and cyclopropyl carbinol derivatives using TMSBr, DMPSCl and TMSN 3 as nucleophiles has been developed. A variety of acyclic tertiary alkyl bromides, chlorides and azides were therefore prepared with excellent diastereopurity. The substitution occurs at the most substituted quaternary carbon center in a stereoinvertive manner, which may be attributed to the existence of a bicyclobutonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…This is what was observed for 2b (Figure 1A). Similarly, during the preparation of this manuscript, Marek reported similar reactions involving CPC cations [40][41][42] and showed that phenyl-containing substrates, when reacted with highly nucleophilic trialkylaluminum compounds at lower temperatures, provide the homoallyl products without any epimerization. 40 This supports our conclusion of a CPC/homoallyl kinetic competition as the driver of the selectivity.…”
Section: Figure 1 Free Energies In Kcal/molmentioning
confidence: 75%
“…This is what was observed for 2b (Figure 1A). Similarly, during the preparation of this manuscript, Marek reported similar reactions involving CPC cations [40][41][42] and showed that phenyl-containing substrates, when reacted with highly nucleophilic trialkylaluminum compounds at lower temperatures, provide the homoallyl products without any epimerization. 40 This supports our conclusion of a CPC/homoallyl kinetic competition as the driver of the selectivity.…”
Section: Figure 1 Free Energies In Kcal/molmentioning
confidence: 75%
“…For instance, Feringa, Houk and Fujita reported in 2018 that cycloheptenyl bromide III undergoes an enantiospecific rearrangement to its cyclohexenyl derivative IV under Lewis acid catalysis, a process that involves CPC cation V. 44 Similarly, Marek has published a series of reports starting in 2020, discussing how cyclopropylcarbinols VI form homoallylic products VII with high diastereoselectivity, as long as no aromatic substituent is located at the R 3 or R 4 positions. [45][46][47][48][49][50] Our group studied this system computationally and showed that CPC intermediate VIII is responsible for the observed selectivity. 51 This cation only rearranges faster than nucleophilic trapping when R 3 is an aryl substituent, which enables a classical homoallylic cation to intervene, leading to reduced specificity.…”
mentioning
confidence: 99%